2011
DOI: 10.1016/j.envpol.2010.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and seasonal variation of atmospheric bulk deposition of polycyclic aromatic hydrocarbons in Beijing–Tianjin region, North China

Abstract: Bulk deposition samples were collected in remote, rural village and urban areas of Beijing–Tianjin region, North China in spring, summer, fall and winter from 2007 to 2008. The annually averaged PAHs concentration and deposition flux were 11.81 ± 4.61 µg/g and 5.2 ± 3.89 µg/m2/day respectively. PHE and FLA had the highest deposition flux, accounting for 35.3% and 20.7% of total deposition flux, respectively. More exposure risk from deposition existed in the fall for the local inhabitants. In addition, the PAHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…The result of PAHs was corresponding with Qi et al's study, probably resulting from the coal burnings in winter (Qi et al, 2011) and the higher atmospheric deposition in the cold period (Wang et al, 2011). Compared with the influent of WWTPs in other cities of the world (Table 2), PAHs were present at lower concentrations in this work (0.37 AE 0.06 mg/L in summer and 0.75 AE 0.07 mg/L in winter).…”
Section: Concentrations Of Spahs and Pahs In The Dissolved Phase Samplessupporting
confidence: 65%
“…The result of PAHs was corresponding with Qi et al's study, probably resulting from the coal burnings in winter (Qi et al, 2011) and the higher atmospheric deposition in the cold period (Wang et al, 2011). Compared with the influent of WWTPs in other cities of the world (Table 2), PAHs were present at lower concentrations in this work (0.37 AE 0.06 mg/L in summer and 0.75 AE 0.07 mg/L in winter).…”
Section: Concentrations Of Spahs and Pahs In The Dissolved Phase Samplessupporting
confidence: 65%
“…The result suggested that sources for target compounds in the rivers besides WW and WWTP effluent might exist. Wang et al (2011b) have demonstrated that the atmospheric deposition is an important pathway for the PAHs to enter the aquatic environment in the Beijing-Tianjin region. Not only the concentrations of PAHs in the deposition particles, but also the deposition fluxes in the heating season were higher than those in the non-heating season, as a result of more coal and biomass burning sources during the heating season in this region.…”
Section: Seasonal Variation In the Particulate Samplesmentioning
confidence: 99%
“…The deposition flux in study area was comparable to those previously study in south China, it was higher than that report in more industrialized or urbanized region like Pearl River Delta, China during 2003e2004 (140 ± 89 mg m À2 yr À1 ) (Li et al, 2010), but it was slight lower than the report value at Guangzhou during 2001e2002 (mean 460 mg m À2 yr À1 ) (Li et al, 2009). The flux was much less than the value in north China, where the deposition flux was 5.22 ± 3.89 mg m À2 day À1 in BeijingTianjin region (Wang et al, 2011), 4.88 mg m À2 day À1 in Tianjin and 5.14 mg m À2 day À1 in the rural of Beijing. Compared with other rural or suburban area in the world, the result was of same order of magnitude as that reported in the rural of southern Germany (73.49e388.01 mg m À2 yr À1 ) (Gocht et al, 2007), however it was higher than that in the suburban in the Seine Basin of France (47.85 mg m À2 yr À1 ) (Motelay-Massei et al, 2003), and that in remote site of northern Spain (60.5 ± 16.4 mg m À2 yr À1 ) (Foan et al, 2015).…”
Section: General Characteristic Of Annual Deposition Fluxesmentioning
confidence: 91%
“…Hence, the total deposition can be expressed by the sum of wet and dry deposition, namely "bulk" deposition, which does not discriminate any of the processes and, as a consequence, it sums up all of them (MotelayMassei et al, 2003;Gocht et al, 2007;Esen et al, 2008;Zhang et al, 2008;Wang et al, 2011). Transport and fate of PAHs in the atmospheric bulk deposition partly depended on their physicochemical characteristics, atmospheric concentration, meteorological condition, topography and emission density (Gocht et al, 2007;Esen et al, 2008;Wang et al, 2011;Zhong and Zhu, 2013). Conversely, the atmospheric deposition affected on the equilibrium partitioning of semi-volatile organic chemicals (SOCs) between air and surface, and finally had a strongly influence on the long-term distribution of SOCs in the regional/global environment.…”
Section: Introductionmentioning
confidence: 99%